Isolation, characterization and identification of microbes in biofertilizer - Mohd Farid, Ishak (2008)
Biofertilizer has been identified as an alternative to chemical fertilizer to increase soil fertility and crop production in sustainable farming. The objectives of this study are to isolate microorganism in biofertilizer and to study the characteristic of microbe that can enhance the uptake of macronutrient which is nitrogen (N), potassium (K) and phosphate (P). This study involves with isolation of microbes in biofertilizer, which can enhance the uptake of macronutrient. After that, the microbes are characterized using three staining methods which are gram staining, acid-fast staining and spore staining also the catalase test to determine the type of microbes. The morphology of microbes can be observed after all the staining process is done by observing the colour change and the shape of each microbe. In the nut shell, characterization of this microbe can be done by doing three steps of staining methods and catalase test.